Wearable Sensors in Clinical Toxicology: Balancing Technological Promises with Methodological and Pragmatic Constraints - Ahmet Nurhak Çakır (Eurasian Journal of Toxicology, 2026)
Since this manuscript is submitted as a Letter to the Editor, no abstract is required in accordance with the journal's guidelines.